The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1073/pnas.1920427117
|View full text |Cite
|
Sign up to set email alerts
|

Closing and opening of the RNA polymerase trigger loop

Abstract: The RNA polymerase (RNAP) trigger loop (TL) is a mobile structural element of the RNAP active center that, based on crystal structures, has been proposed to cycle between an “unfolded”/“open” state that allows an NTP substrate to enter the active center and a “folded”/“closed” state that holds the NTP substrate in the active center. Here, by quantifying single-molecule fluorescence resonance energy transfer between a first fluorescent probe in the TL and a second fluorescent probe elsewhere in RNAP or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 49 publications
(158 reference statements)
2
23
0
Order By: Relevance
“…This characteristic shape of distributions points to the presence of several sequential rate-limiting steps, as expected from the presence of multiple cycles of nucleotide addition for a single KF-binding event. 33 , 34 , 35 There was not a large shift in the polymerisation times between 5-nt and 10-nt extensions, with the mean polymerisation time only increasing from 1.9 s for 5-nt extensions to 2.2 s for 10-nt extensions. This suggested that the bases between the 5–10 positions may be incorporated faster that the bases between positions 1–5.…”
Section: Resultsmentioning
confidence: 85%
“…This characteristic shape of distributions points to the presence of several sequential rate-limiting steps, as expected from the presence of multiple cycles of nucleotide addition for a single KF-binding event. 33 , 34 , 35 There was not a large shift in the polymerisation times between 5-nt and 10-nt extensions, with the mean polymerisation time only increasing from 1.9 s for 5-nt extensions to 2.2 s for 10-nt extensions. This suggested that the bases between the 5–10 positions may be incorporated faster that the bases between positions 1–5.…”
Section: Resultsmentioning
confidence: 85%
“…In the crystal structures of this work, as in the crystal structures of refs. 27 and 28 , RNA products generated by reiterative transcription initiation were limited in length because further RNA extension was blocked by the presence of the σ finger in the RNAP active-center cleft and by crystal-lattice constraints that prevented displacement of the σ finger from the RNAP active-center cleft ( 35 , 37 ), opening of the RNAP clamp ( 39 41 ), or any other conformational change that could open a path for further extension of RNA and for extrusion of RNA from the RNAP active-center cleft. One hypothesis is that, in solution, complete displacement of the σ finger from the RNAP active-center cleft channel could allow long RNA products generated in reiterative transcription initiation to exit the RNAP active-center cleft through the RNAP RNA-exit channel, the same exit route used by RNA in standard transcription ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using smFRET have revealed various aspects of dynamics during the transcription initiation and transition states ( 17 , 26 , 31 , 62 , 69 , 70 , 107 , 108 , 109 , 110 , 111 ). Typically, to visualize the conformational changes during initiation, FRET-pair dyes, such as Cy3 and Cy5, can be attached to RNAP subunits ( Fig.…”
Section: Single-molecule Methods In Transcription Studiesmentioning
confidence: 99%